Grundtvigs oversættelser af græske salmer - Hansen, Uffe (Grundtvig-Studier, 1953)
Grundlvig's Translations of Greek Hymns. By Uffe Hansen. In his "Sang-Værk" (1837) Grundtvig sought to collect together various hymns of the principal Churches , with several translated from foreign languages - 37 of them from Greek. While the other tran slations and adoptations are furnished with such copi ous notes that it is easy to find their originals, this is not the case with the translations from Greek. They are provided only with scanty notes like: "From an Anciet Greek Easter Hymn"; "Composed on themodel of a Greek Christmas Hymn"; "From the Greek Hymn for Passion Week"; "A Greek Hymn". Since he did not indicate his source in any other way, it is very difficult now to find it; and previous tesearehers have only indicated very few of the originals. A. G. Rudelbach pointed out in 1856 that No. 122 in "Sang-Værk" was taken from Clement of Alexandria's Hymn to the Saviour in the end of the 3rd hook of Paidagogos", and O. E. Th).lner in "Dansk Salme-Leksikon ". 1931, gives information about Nos. 211, 217, 219, 220 and 332, which are all to be found in Christ et Paranikas: Anthologia Graeca Carminium Christian orum . Among the manuscripts of Grundtvig's hymns is a draft of I, 200, where on the blank back of a page ther are noted down 21 lines from Greek hymns, apparently the first lines of a number of hymns which Grundtvig had thought of translating. But only one of them, marked with a cross in the manuscript, is translated in "Sang-Værk", i.e., No. 220. But since both these first lines and also the footnotes in "Sang-Værk" suggested that Grundtvig had found his origina ls in a fairly large collection of hymns, probably a hymn-book which was in actual use, I got hold of the hymn-books of the Greek Orthodox Church and found there, first, all the hymns beginning with the lines mentioned above, and, foliowing this, 25, in all, of the 37 hymns translated by Grundtvig. Probably the remainder are also to be found there; but it is often hard to deeide which Greek text Grundtvig has used, because several Greek hymns are very like each other and the trans lation is often very free. Most af the hymns are from the 8' century or earlier, and are to be found in "Triodion", "Pentekostarion ", "Parakletikon", and in the twelve volumes of "Menaion", which has a volume for each month. Even if Grundtvig 's translations have to some degree changed the originals, still they bear such clear marks of their origin that one can speak of them as bringing a contribution of Greek spiritual life and the Greek form of Christianity to "Sang-Værk" and thereby to some extent to Danish hymnology. Full justice is done here to the free and joyo us tone which prevails in the Greek hymns, and Grundtvig undoubtedly felt himself attracted and allowed himself to be influenced by it, as well as by some individual features of those hymns, such as the reference to the women mention ed in the Gospel, "the women bearing myrh", and especially the woman who was a sinner "with her jar of alabaster". But side by side with the gentie notes of the Greek hymns Grundtvig can sometimes set his own firm and even polemic tone, so that a translation of a Greek hymn can have introduced into it a sharp criticism of the deviations of the Greek Creed from the Apostolie Creed -see No.332, where the Nicean Creed is called "empty quaverings, whose tone is set by heathen whims".